Perancangan Sistem Informasi Akuntansi Pendapatan Pajak Kendaraan Bermotor Pada Cabang Pelayanan Pendapatan Daerah - Renna Marziana Syadiani (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2018)
Branch of area service revenues which is located at jl. Kawaluyaan Raya, bandung. This company is usually executing their earnings transction of quotation process in maually. This problems result is not effectiveness and maximum the performamce of all section at the company about supplying of information and report that is needed by the company its self. According to those problems the writer tries to find the suitable title for thatâ€™s problem, so that this final Assisgment will be useful for the future. Finally the writer chooses the tittle of final Assigment â€œDesigning Motorized Tax Revenue Accounting Information System at Regional Revenue Serviceâ€. The writer uses the design of research with Primary/Secondary dataâ€™s, the type of research uses the qualitative and quantitative dataâ€™s, then. The method using exploratory and descriptive and research, next the technique of collecting dataâ€™s using field study which consisted of interview, observation and book study. The method of development system uses the methodologies which orienting at process, dataâ€™s and output. The writer using the stucture of development system is Waterfall. The writer uses completeness system is Normalization, context Diagram, Data flowDiagram (DFD), entity relationship diagram, Dictionaries of dataâ€™s and flowchart. There is representing of input from the Quotation dataâ€™s. The process consist of General Journal and general ledge. Furthermore, the output consist of financial statement balance sheet and financial statement of profit and loss. So that, this result of final Assigment could optimally make the report which this company needed is easier with final Assigment.